A longitudinal analysis of mental and general health status of informal carers in Australia - Itismita Mohanty; Theo Niyonsenga (BMC, 2019)
Abstract Background The study investigated the self-assessed mental and general health status of informal carers in Australia. It evaluated the influence of carer's health behaviours, namely physical activity, smoking and drinking status, along with their social connectedness and workforce engagement on their health status. Methods The study used a retrospective longitudinal design using data from the Household Income and Labour Dynamics of Australia survey, waves 5-15 (2005-2015). It included individuals aged 15 years and older from Australian households surveyed over a period of 11 years. The sample consisted of 23,251 individuals. The outcome measures included: mental health, general health and physical functioning domains of the Short Form 36 Questionnaire, a widely used multi-dimensional measure of health-related quality of life. Using fixed effects regression and following individuals over time, the analysis took care of the issue of individuals self-selecting themselves as carers due to some predisposing factors such as age, poor health, socioeconomic status and sedentary behaviour. Results There were statistically significant carer-noncarer status differences in mental (Beta = − 0.587, p = 0.003) and general health (Beta = − 0.670, p = 0.001) outcomes. Aging had a modifying impact on carers' mental and general health outcomes. Older carers coped better with their caregiving responsibilities than younger ones. Moreover, while physical activities had a positive influence on both mental and general health for non-carers, with more activities generating better health outcomes, it only had a modifying impact on carers' mental health. Furthermore, the study found that moderate levels of social drinking had beneficial modifying impact on carers' mental and general health. Conclusion This study added value to the literature on informal carers' mental and general health in Australia by identifying some of the protective and risk factors. The study found the modifying effects of carers' age, health behaviours such as physical activity, smoking and drinking status on their health. Finally, the study identified an apparent beneficial link between moderate levels of social drinking and carer health that needs to be further explored with more targeted future research.